A case control study of possible additional risk factors for chronic alcoholic pancreatitis - Gopal, Sri Vengadesh; Solomon, Ashley; Konidala, Jaahnavi (International Journal of Research in Medical Sciences, 2016)
Background: Chronic pancreatitis (CP) is characterised by irreversible damage to pancreas leading to endocrine and exocrine insufficiency with considerable morbidity. Etiopathogenesis is multifactorial with interplay between genetics & environmental toxins. Alcoholism is more commonly associated with chronic pancreatitis. But it is not very clear why only certain proportion of the alcoholics develop pancreatitis. So this study was conducted to find the possible additional risk factors involved in alcoholic pancreatitis. Methods: A total of 30 patients with alcoholic pancreatitis from a tertiary care hospital in Pondicherry, India were enrolled and compared with age matched alcoholics without pancreatitis. The diagnostic criteria for alcoholism were based on diagnostic and statistical manual of mental disorders (DSM) criteria IV of alcohol consumption >80gms/day for a period of 5 years or more and chronic pancreatitis was based on significant clinical findings and positive ultrasound findings of pancreatitis. Questions regarding additional risk factors of pancreatitis like smoking, blood group and Diabetes mellitus were asked and recorded using the standard questionnaire. Results: Smoking history was noted in 73% of cases and 63.4% of controls. Non O blood group was noted in 56.6% of cases and 46.6% of controls. 10% of cases and 6.6% of controls gave history of diabetes before the development of pancreatitis. The additional risk factors were almost similar in both the groups and there was no statistical difference. Conclusions: It was concluded that there is no statistically significant additional risk factors for chronic alcoholic pancreatitis noted in present study and a study with a large sample size for an extended period is recommended.